Answer:
[tex]\frac{6}{x}-\frac{7}{y}=\frac{7}{12}[/tex]
Step-by-step explanation:
#We know that the filling taps will run for a cumulative 4hrs each while the draining hole will empty for a combined 7hrs.
Let x be the rate of the first filling tap, and 2x of the 2nd filling tap and y be the rate of the hole.
#The rate at which the tub fills per hour is :
[tex]V_{tub}=\frac{1}{x}+\frac{1}{2x}-\frac{1}{y}\\\\=\frac{1}{x}(1+\frac{1}{2})-\frac{1}{y}\\\\=\frac{3}{2x}-\frac{1}{y}[/tex]
#The volume of the tub at the instant moment the leak is repaired is expressed as:
[tex]V_{tub}=\frac{3}{2x}t_1-\frac{1}{y}t_2=\frac{7}{12}, \ \ \ \ \ \ t_1=4,t_2=7\\\\\\\frac{3}{2x}\times 4-\frac{1}{y}\times7\frac{7}{12}\\\\\\\frac{6}{x}-\frac{7}{y}=\frac{7}{12}[/tex]
Hence, the volume of the tub after the leak is repaired is expressed as [tex]\frac{6}{x}-\frac{7}{y}=\frac{7}{12}[/tex]